2015
DOI: 10.1517/14740338.2015.1061500
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the safety of chemotherapy for treating breast cancer during pregnancy

Abstract: The rule of thumb of chemotherapy - avoiding first trimester exposure and starting therapy in the second trimester - can be considered applicable for classic agents that are used in managing pregnant breast cancer patients. Anthracycline-based regimens are considered the standard of care in managing BCP. Recently, a growing amount of data suggests the safety of taxanes during pregnancy. Pregnancy in cancer patients should be considered as "high risk": once the systemic treatment is initiated, regular fetal mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…Experts argue that women can and should be reassured that the drugs used to treat GBC do not adversely affect the foetus if they are administered in the second and third trimesters and that treatment should not be delayed (Amant et al, 2015;Lambertini et al, 2015). All participants expressed considerable worry about the effects of treatment on the health of the foetus.…”
Section: The Bodymentioning
confidence: 99%
“…Experts argue that women can and should be reassured that the drugs used to treat GBC do not adversely affect the foetus if they are administered in the second and third trimesters and that treatment should not be delayed (Amant et al, 2015;Lambertini et al, 2015). All participants expressed considerable worry about the effects of treatment on the health of the foetus.…”
Section: The Bodymentioning
confidence: 99%
“…As with any medical condition in pregnancy, it is important to evaluate the perinatal effects of breast cancer for both mother and fetus. A few such studies have been conducted but they were small in size and heterogeneous in nature . The purpose of our study is to evaluate the incidence of PABC and the effect of breast cancer in pregnancy on the fetus using a large population‐based cohort of women delivering in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Lambertini, et al concluded that there is usually enough time to use a multidisciplinary approach regardless of the gestational age at which diagnosis is made. However, despite the amount of data on chemotherapy use during pregnancy, the review noted that treatment recommendations of these women rely on limited evidence and that there were no specific guidelines for monitoring individuals with prenatal exposure to agents [1,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Adriamycin and cyclophosphamide are generally well tolerated in pregnancy and suggested to be two of the chemotherapy drugs of choice for treatment of PABC in a recent expert opinion published by Lambertini, et al in which he reviews the literature to date which is admittedly limited of the safety profile of these drugs during pregnancy. The most common medical side effect of these drugs is myelosuppression in both the mother and fetus [3,5,7,9,12,13]. In one study, Rouzier demonstrated the chemosensitivity to these drugs was the same in tumors of PABC and tumors of non-pregnancy associated breast cancers [3,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation